Physical education in bilingual projects 1st cycle - Ortiz Calvo, Antonio
This teaching guide is a resource for Physical Education teachers involved in Bilingual projects, that is to say, teachers either with the Physical Education and English specialities qualifications or páginas:E teachers with a least a B2 level of English according to the Common European Framework of Reference (CEFR). This guide therefore addresses the challenge in which teachers enrolling in bilingual projects find themselves in. Even the most experienced teachers need to widen their knowledge bringing themselves up to date when dealing with a new subject to be taught in English. The latest researches have identified that the main problems that teachers face with a bilingual project are the following: Insecurity, lack of specific and technical vocabulary, lack of fluency in a new teaching context and lower external support such as text books, audios, and digital resources. Thus, teachers need to face a new teaching situation; involving new and specific vocabulary. Furthermore, all the oral explanations and prompts are to be done by themselves without any external support unlike what normally happens in the classroom.